Multiplex enhancer-reporter assays uncover unsophisticated TP53 enhancer logic - Verfaillie, Annelien; Svetlichnyy, Dmitry; Imrichova, Hana; Davie, Kristofer; Fiers, Mark; Kalender Atak, Zeynep; Hulselmans, Gert; Christiaens, Valerie; Aerts, Stein

(untitled) (Genome Research, 2016)
Transcription factors regulate their target genes by binding to regulatory regions in the genome. Although the binding preferences of TP53 are known, it remains unclear what distinguishes functional enhancers from nonfunctional binding. In addition, the genome is scattered with recognition sequences that remain unoccupied. Using two complementary techniques of multiplex enhancer-reporter assays, we discovered that functional enhancers could be discriminated from nonfunctional binding events by the occurrence of a single TP53 canonical motif. By combining machine learning with a meta-analysis of TP53 ChIP-seq data sets, we identified a core set of more than 1000 responsive enhancers in the human genome. This TP53 cistrome is invariably used between cell types and experimental conditions, whereas differences among experiments can be attributed to indirect nonfunctional binding events. Our data suggest that TP53 enhancers represent a class of unsophisticated cell-autonomous enhancers containing a single TP53 binding site, distinct from complex developmental enhancers that integrate signals from multiple transcription factors.